STRUKTUR MANTRA KEKUATAN DALAM BUKU “JANGJAWOKAN INVENTARISASI PUISI MANTRA SUNDA”: KAJIAN ETNOLINGUISTIK - Aulia Pebrianti Wardani; Nani Darmayanti; Agus Nero Sofyan (Kajian Linguistik dan Sastra, 2021)
AbstrakThis research is entitled "Structure of Mantra Strength in the Book "Jangjawokan Inventarisasi Puisi Mantra Sunda": Ethnolinguistics Study " motivated by the writer's interest in Sundanese. The purpose of this study is to describe the structure contained in the power mantra. The method used in this study is a qualitative method with a follow-up method, namely listening method that is done by listening, which is harmonized with the observation method. And data collection techniques in this study using recording techniques, namely recording data from primary sources in the form of books from the Department of Tourism and Culture of West Java ProvinceThe analyzed of mantra strength totaled five data. Based on the results of data analysis of power spells, it can be concluded that the structure of power spells in one stanza of spells is erratic, has irregular rhymes and all spells have a repeated rhythm. Having a physical structure and an inner structure. The physical structure of a power spell consists of diction, images, concrete words, figurative language, rhyme and rhythm. While the inner structure of the mantra consists of theme, feeling, tone, and message.The mantra also shows the use of words that are very close to the culture and existence of the Sundanese people, such as Ajian macan putih, Nyi Sri Girintil, Monyet, Batara Guru and other words that are closely related to Sundanese society. In addition, it can be seen that the supernatural beliefs are inseparable from a number of forms of rituals and daily activities that show the beliefs of the Sundanese people in religious life.